DEVELOPMENTS OF INSTRUCTIONAL MODELS BASED ON MATHEMATICS COMMUNICATION SKILLS IN INTEGRAL CONCEPTS AND APPLICATIONS - Awaludin Awaludin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The problem of this research is the low mathematical communication skills of students in integral calculus courses. The purpose of this study was to develop a learning model based on Mathematical Communication skills on integral concepts and applications, and to determine the feasibility and effectiveness of learning models based on Mathematical Communication skills on integral concepts and applications. This research method is a research and development method. The research subjects were 43 students of the Mathematics Education Department at Halu Oleo University. Data collection techniques using questionnaires, interviews and test techniques. Data analysis was carried out in a quantitative and qualitative descriptive manner. The results of the data analysis showed that the integral concept and application learning materials based on the assessment of mathematics learning experts and learning design experts reached 86.3% and 89.16% in the very good category. While the results of the student assessment showed 87.5%. The small group evaluation results showed an average percentage of 88.2% with a very good category. The results of the large group trial reached a percentage value of 90.1% in the very good category. Therefore, the development of a learning model is able to improve students' mathematical communication skills on integral concepts and applications